2018
DOI: 10.3390/nu10101508
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Program Intervention with Reduced-Iron Multiple Micronutrient Powders on Iron Status, Morbidity and Growth in Young Children in Ethiopia

Abstract: Despite the potential for improving iron status and child growth in low- and middle-income settings, concerns on the safety of high iron dosages of Micronutrient Powders (MNP currently limit their applicability in programs. We examined the effectiveness and risks of an integrated complementary feeding program with low iron dose (6 mg/serving) MNP among 6–23-month-old Ethiopian children using a quasi-experimental study design comparing children from five intervention districts (n = 1172) to those from four matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 32 publications
0
40
0
3
Order By: Relevance
“…Of these studies, 121 studies were randomized controlled trials , 57 were cluster randomized controlled trials , 11 were non-randomized controlled trials [218][219][220][221][222][223][224][225][226][227][228], 2 were natural experiments [229,230], 4 were controlled before-after studies [231][232][233][234], 1 was an interrupted time-series study [235], and 1 was a propensity score matched retrospective cohort study [236]. 86 studies were conducted in Asia [43,48,49,54,55,57,[59][60][61][62]69,[72][73][74][75][76][78][79][80]83,86,87,92,97,98,107,110,117,[119]…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Of these studies, 121 studies were randomized controlled trials , 57 were cluster randomized controlled trials , 11 were non-randomized controlled trials [218][219][220][221][222][223][224][225][226][227][228], 2 were natural experiments [229,230], 4 were controlled before-after studies [231][232][233][234], 1 was an interrupted time-series study [235], and 1 was a propensity score matched retrospective cohort study [236]. 86 studies were conducted in Asia [43,48,49,54,55,57,[59][60][61][62]69,[72][73][74][75][76][78][79][80]83,86,87,92,97,98,107,110,117,[119]…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…A recent national micronutrient survey found that 34% of children under 5 years of age experience anaemia, 18% are iron deficient, 14% vitamin A deficient and 35% zinc deficient (Ethiopian Public Health Institute, ). Point‐of‐use fortification of complementary foods with MNP has been demonstrated to improve growth and haemoglobin status among Ethiopian children 6–23 months of age (Samuel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent national micronutrient survey found that 34% of children under 5 years of age experience anaemia, 18% are iron deficient, 14% vitamin A deficient and 35% zinc deficient (Ethiopian Public Health Institute, 2016). Point-of-use fortification of complementary foods with MNP has been demonstrated to improve growth and haemoglobin status among Ethiopian children 6-23 months of age (Samuel et al, 2018). A theory-driven, mixed-method, formative process evaluation was conducted to elucidate how the intervention worked, with the goal of determining what aspects of program delivery and adherence went well, identifying where problems occurred and understanding the magnitude and causes of problems.…”
mentioning
confidence: 99%
“…Empat studi memberikan intervensi mikronutrien dalam bentuk bubuk/tablet dengan berbagai model atau jenis. Intervensi yang diberikan berisi mikronutrien antara lain energi, protein, lemak, karbohidrat, kalsium, fosfat, sodium, potassium, magnesium, iron, zinc, iodine, manganese, copper, niacin, thiamin, riboflavin, taurine, pantothenic acid, folat, choline, biotin, selenium, chloride, retinol, phosphorus, vitamin (A,B,C,D,E,K) (Christian et al, 2015;Hess et al, 2015;Phuka et al, 2009;Samuel et al, 2018 (A,C,D) dan membandingkan dengan kelompok kontrol yang diberikan formula rendah kalori dan rendah protein (Lebenthal et al, 2014;Yackobovitch-Gavan et al, 2016). Pemberian mikronutrien pada kelompok intervensi meningkatkan tinggi badan (p<0.001) dan berat badan (p = 0.005) pada anak yang termasuk dalam kategori "good consumer" atau mengkonsumsi >50% formula yang diberikan.…”
Section: Tabel 1 Artikel Pendidikan Kesehatan Dan Stimulasi Responsiveunclassified
“…Terdapat juga peningkatan konsentrasi Hb (+2.4 ± 1.2 g/L) pada kelompok intervensi sedangkan pada kelompok kontrol mengalami penurunan konsentrasi Hb (Samuel et al, 2018). Peningkatan TB dan BB secara signifikan menurunkan prevalensi stunting, wasting, dan underweight (Hess et al, 2015).…”
Section: Tabel 1 Artikel Pendidikan Kesehatan Dan Stimulasi Responsiveunclassified